Daraxonrasib, a pan-RAS inhibitor, selectively inhibits osteosarcomas with activated KRAS by halting AKT signaling and matrix metalloprotease activity - Jung, Okkeun; Soto, Angelene; Wolfe, Andrew L.; Mahajan, Shahana S. (PLOS ONE, 2025)
KRAS mutations, which induce proliferative signaling driving many human cancers, are detectable in a small subset of osteosarcoma patients. The recently developed pan-KRAS inhibitor daraxonrasib, also known as RMC-6236, is capable of targeting a wide array of KRAS mutations and shows promise against pancreatic and lung cancers. However, the efficacy and mechanisms of action of daraxonrasib in osteosarcoma (OS) remain unclear. We evaluated the effects of daraxonrasib on the viability, proliferation, and metastatic potential of wild-type and KRAS mutant OS cells. We assayed the effects of treatment on downstream targets using qPCR, immunoblotting, and activity assays to explore the underlying mechanism by which daraxonrasib selectively suppresses the metastatic potential of KRAS mutant osteosarcoma. Finally, we investigated how the increased prevalence of GTP-bound KRAS enhanced the sensitivity of KRAS wild-type osteosarcoma cells to daraxonrasib using siRNA targeting RASA1. Daraxonrasib selectively attenuated the proliferation and migratory ability of KRAS mutant HOS-143B cells without affecting KRAS wild-type controls. Additionally, daraxonrasib suppressed the expression of the matrix metalloproteases MMP9 and MMP1, which promote cell motility and metastasis. Daraxonrasib selectively inhibited the AKT/ETS1 pathway in HOS-143B cells, whereas no such effect was observed in HOS cells. HOS cells were sensitized to daraxonrasib by knocking down the GTPase-activating protein RASA1. In osteosarcoma, KRAS inhibition decreased MMP1, MMP9, and AKT/ETS1 signaling. Daraxonrasib is a promising agent for treating osteosarcoma with KRAS mutations.